2020
DOI: 10.3390/cells9112506
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Precursor Protein APP Down-Regulation Alters Actin Cytoskeleton-Interacting Proteins in Endothelial Cells

Abstract: The amyloid-β precursor protein (APP) is a ubiquitous membrane protein often associated with Alzheimer’s disease (AD) and cerebral amyloid angiopathy (CAA). Despite its role in the development of the pathogenesis, APP exerts several physiological roles that have been mainly investigated in neuronal tissue. To date, the role of APP in vasculature and endothelial cells has not been fully elucidated. In this study, we used molecular and proteomic approaches to identify and investigate major cellular targets of AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Accordingly, BBB integrity may be disrupted in some of the patients with SZ, causing BBB leakage. Additionally, the imbalances observed in BECs-related growth factors in SZ [61 ▪▪ ,71 ▪▪ ,77 ▪▪ ,79 ▪ ,82,83] might be translated into an altered BBB integrity and function after stressful events [75].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, BBB integrity may be disrupted in some of the patients with SZ, causing BBB leakage. Additionally, the imbalances observed in BECs-related growth factors in SZ [61 ▪▪ ,71 ▪▪ ,77 ▪▪ ,79 ▪ ,82,83] might be translated into an altered BBB integrity and function after stressful events [75].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, a meta-analysis reported unaltered MCP1 blood levels among drug-naive first-episode SZ ( [72,73]. Amyloid precursor protein (APP) is highly expressed in murine endothelium during the first stages of embryogenesis [74] and in-vitro studies indicated a positive effect of APP on endothelial cells migration, proliferation [75] and nitric oxide production [76]. CSF measurements of 11 different growth factors associated with neuro-plasticity indicated lower levels of APP and GDNF in SZ (94 SZ and 118 controls) [77 && ].…”
Section: Evidence From Peripheral and Cerebrospinal Fluid Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in multiple cell types suggest that APP regulates integrin-mediated adhesion, a function consistent with the ubiquitous expression of both proteins. The loss of APP in endothelial cells reduces expression of β1-and β3-integrins, compromising attachment of cells to collagen and fibronectin substrates ( Ristori et al, 2020 ). Adhesion of THP-1 monocytes to collagen substrates is also dependent on APP expression, wherein adhesion induces the formation of a receptor complex containing β1-integrins and APP, initiating MAPK signaling and facilitating monocyte activation ( Sondag and Combs, 2004 ) ( Figure 4A iii).…”
Section: Interactions Of Cams With App and The Role That Cams Play In...mentioning
confidence: 99%
“…For instance, integrins recruit their cytoplasmic adaptors (e.g., kindlin and talin) via a cytoplasmic NPxY motif, and this event ultimately affects the remodeling of the actin cytoskeleton 42 . Similarly, the NPxY-binding APP intracellular adaptors converge to the same cytoskeletal actin pathway 4,23 (table 1). Notably, APOE lipoprotein receptors also recruit the same NPxY motif for signaling (as shall be discussed in the next sections).…”
Section: App May Be a Synaptic Adhesion Molecule: The Evolutionarily-conserved Npxy Motifmentioning
confidence: 99%